Multiple field tests on landing day: Early mobility may improve postural recovery following spaceflight - Rosenberg, Marissa J.; Reschke, Millard F.; Tomilovskaya, Elena S.; Wood, Scott J. (Frontiers in Physiology, 2022)
Adaptation to microgravity causes astronauts to experience sensorimotor disturbances during return to Earth that lead to functional difficulties. Recently, the Field Test (FT) study involving an incrementally demanding sensorimotor functional test battery has allowed for an unprecedented view into early decrements and recovery from multiple tests conducted on the landing day following 6-month International Space Station missions. Although the protocol was challenging and temporarily increased motion sickness symptoms, there were anecdotal reports that performing these tasks within the first few hours of landing accelerated their recovery. Here, to investigate these anecdotal reports, we present results from a computerized dynamic posturography (CDP) that all crewmembers perform upon return to Houston and compare performance between crewmembers that participated in FT (n=18) with those that did not (controls, n=11). While there were significant decrements in postural performance for both groups, some FT participants tended to perform closer to their preflight baseline in the most challenging condition of the CDP sensitive to vestibular function – eyes closed, unstable support and head movements. The effect size for mean pre-to-postflight differences between FT and control groups was 0.78 in this condition. We attribute this serendipitous observation to the manner in which the field tests were implemented – encouraging early movement to drive adaptation but performed in a constrained incremental fashion to minimize movements above aversive thresholds. Challenging the sensorimotor system with increasingly provocative movements performed as close to landing as possible could be a useful intervention to accelerate astronaut’s sensorimotor readaptation that deserves further study.